The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/dac.3253
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the moderating effect of trust on the adoption of cloud‐based services

Abstract: Cloud computing provides a way to coordinate and share relevant information and data on real-time basis over an organization. The adoption of cloud services is one of the most emerging technological advances in the practice of current competitive business environment. The research done in this article is based on the analysis of the data obtained from the semiconductor sector. Cloud adoption would most likely be the best answer for them. However, because of various types of complexities, semiconductor industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Rahi et al 34 have also confirmed the impact of trust issues on the technological success factors of cloud services adoption in semiconductor firms. Elmonem et al 33 studied cloud computing applications for ERP systems and found out the performance risks along with security risks, customization, and integration as those challenges which topped the list of cloud ERP adoption challenges continuously every year during 2011 to 2016.…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…Rahi et al 34 have also confirmed the impact of trust issues on the technological success factors of cloud services adoption in semiconductor firms. Elmonem et al 33 studied cloud computing applications for ERP systems and found out the performance risks along with security risks, customization, and integration as those challenges which topped the list of cloud ERP adoption challenges continuously every year during 2011 to 2016.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Elmonem et al 33 studied cloud computing applications for ERP systems and found out the performance risks along with security risks, customization, and integration as those challenges which topped the list of cloud ERP adoption challenges continuously every year during 2011 to 2016. Rahi et al 34 have also confirmed the impact of trust issues on the technological success factors of cloud services adoption in semiconductor firms.…”
Section: Literature Reviewmentioning
confidence: 82%
“…modeling cloud technology adoption in organizations S42 (Ho et al, 2017) Trust or consequences? Causal effects of perceived risk and subjective norms on cloud technology adoption S43 (Hsieh, 2015) Health-care professionals' use of health clouds: Integrating technology acceptance and status quo bias perspectives S44 (Hsieh, 2016) An empirical investigation of patients' acceptance and resistance toward the health cloud: The dual factor perspective S45 (Hsieh and Lin, 2018) Explaining resistance to system usage in the PharmaCloud: A view of the dual-factor model S46 (Hsu and Lin, 2016) Factors affecting the adoption of cloud services in enterprises S47 (Huang, 2016) The factors that predispose students to continuously use cloud services: Social and technological perspectives S48 (Isaias et al, 2015) Outlining the issues of cloud computing and sustainability opportunities and Risks in European organizations: A SEM Study S49 (Jede and Teuteberg, 2016) Understanding socio-technical impacts arising from softwareas-a-service usage in companies (continued) A survey study on major technical barriers affecting the decision to adopt cloud services S69 (Priyadarshinee et al, 2017) Understanding and predicting the determinants of cloud computing adoption: A two staged hybrid SEM-Neural networks approach S70 (Qin et al, 2016) Evaluating the usage of cloud-based collaboration services through teamwork S71 (Rahi et al, 2017) Identifying the moderating effect of trust on the adoption of cloud-based services S72 (Ratnam et al, 2014) A structural equation modeling approach for the adoption of cloud computing to enhance the Malaysian health-care sector (continued) (Ratten, 2016a) Continuance use intention of cloud computing: Innovativeness and creativity perspectives S75 (Ratten, 2016b) Service innovations in cloud computing: a study of top management leadership, absorptive capacity, government support, and learning orientation S76 (Raut et al, 2018) Analyzing the factors influencing cloud computing adoption using three stage hybrid SEM-ANN-ISM (SEANIS) approach S77 (Sabi et al, 2016) Conceptualizing a model for adoption of cloud computing in education S78 (Sabi et al, 2017) A cross-country model of contextual factors impacting cloud computing adoption at universities in sub-Saharan Africa S79 (Sabi et al, 2018) Staff perception towards cloud computing adoption at universities in a developing country S80 (Schniederjans and Hales, 2016) Cloud computing and its impact on economic and environmental performance: A transaction cost economics perspective S81 (Senarathna et al, 2016) Securit...…”
Section: Final Pool Of Articlesmentioning
confidence: 99%
“…Perhaps the greatest worry with cloud data storage is the verification of data integrity at untrusted servers, and how to manage sensitive information. It's not that easy task to keep up client's most sensitive data in cloud environment safely, which is required in numerous applications for clients [18].…”
Section: Integritymentioning
confidence: 99%
“…Integrity ought to be checked at the data and computation level. Data Integrity could help in getting lost data or telling if there is any unauthorized data manipulations [18,19].…”
Section: Integritymentioning
confidence: 99%